2014
DOI: 10.1111/j.1532-950x.2014.12100.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome After Intra‐Articular Administration of Bone Marrow Derived Mesenchymal Stem Cells in 33 Horses With Stifle Injury

Abstract: Objective To report outcome of horses with femorotibial lesions (meniscal, cartilage or ligamentous) treated with surgery and intra‐articular administration of autologous bone marrow derived mesenchymal stem cells (BMSCs). Study Design Prospective case series. Animals Horses (n = 33). Methods Inclusion criteria included horses that had lameness localized to the stifle by diagnostic anesthesia, exploratory stifle arthroscopy and subsequent intra‐articular administration of autologous BMSCs. Case details and fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
144
2
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(155 citation statements)
references
References 41 publications
7
144
2
2
Order By: Relevance
“…Nevertheless, several medications are used intra-articularly, such as COs, hyaluronic acid (HA)/sodium hyaluronate (SH)/hyaluronate (HA), polysulfated glycosaminoglycans, sodium pentosan polysulfate, sodium chondroitin sulfate, somatostatin, N-acetyl- D-glucosamine, radiation synovectomy, dextrose prolotherapy, keratan sulfate orgotein, saline for washout, silicone, mucopolysaccharide polysulfuric acid ester, chloroquine, lactic acid solution, amikacin, gentamicin morphine, autologous serum, platelet-rich plasma, mesenchymal stem cells derived from bone marrow or adipose stromal vascular fraction, gene therapy using IL-1 antagonists, and ethanol. In addition, studies have used a topical liposomal formulation that contains diclofenac, lyophilized products from green-lipped mussel, extracorporeal shockwave, acupuncture, magnetic field, transcutaneous electrical nerve stimulation, therapeutic ultrasound, laser therapy, manual therapy, aquatic physical therapy and nutraceuticals food suplement (Uthman et al 2003;Caron 2005;Revenaugh 2005;Carmona et al 2007;Frisbie et al 2009;Goodrich and Nixon 2006;Santos et al 2009;Lindegaard et al 2010;Cayzer et al 2011;Kawcak et al 2011;Baccarin et al, 2012;McIIwraith et al 2011McIIwraith et al , 2012aCarmalt et al 2012;Lamas et al 2012;Vanderweerd et al 2012;Frisbie et al 2013;King et al 2013;Neuman et al 2013;Ferris et al 2014;Koenig et al 2014, de Grawn et al 2016. The use of controlled physical activity, as a complementary treatment, possibly improves the comfort level of the horse and decreases the inflammatory process (Kerbyson et al 2013).…”
Section: Possible Treatmentsmentioning
confidence: 99%
“…Nevertheless, several medications are used intra-articularly, such as COs, hyaluronic acid (HA)/sodium hyaluronate (SH)/hyaluronate (HA), polysulfated glycosaminoglycans, sodium pentosan polysulfate, sodium chondroitin sulfate, somatostatin, N-acetyl- D-glucosamine, radiation synovectomy, dextrose prolotherapy, keratan sulfate orgotein, saline for washout, silicone, mucopolysaccharide polysulfuric acid ester, chloroquine, lactic acid solution, amikacin, gentamicin morphine, autologous serum, platelet-rich plasma, mesenchymal stem cells derived from bone marrow or adipose stromal vascular fraction, gene therapy using IL-1 antagonists, and ethanol. In addition, studies have used a topical liposomal formulation that contains diclofenac, lyophilized products from green-lipped mussel, extracorporeal shockwave, acupuncture, magnetic field, transcutaneous electrical nerve stimulation, therapeutic ultrasound, laser therapy, manual therapy, aquatic physical therapy and nutraceuticals food suplement (Uthman et al 2003;Caron 2005;Revenaugh 2005;Carmona et al 2007;Frisbie et al 2009;Goodrich and Nixon 2006;Santos et al 2009;Lindegaard et al 2010;Cayzer et al 2011;Kawcak et al 2011;Baccarin et al, 2012;McIIwraith et al 2011McIIwraith et al , 2012aCarmalt et al 2012;Lamas et al 2012;Vanderweerd et al 2012;Frisbie et al 2013;King et al 2013;Neuman et al 2013;Ferris et al 2014;Koenig et al 2014, de Grawn et al 2016. The use of controlled physical activity, as a complementary treatment, possibly improves the comfort level of the horse and decreases the inflammatory process (Kerbyson et al 2013).…”
Section: Possible Treatmentsmentioning
confidence: 99%
“…Besides, BM-MSCs are relatively primitive cells, whose immunogenicity is weak and can inhibit the mixed lymphocyte reaction. However, previous studies also reported the clinical application of BM-MSCs is not matched with donor, host immune rejection or graft versus host reaction (50)(51)(52). Moreover, allogeneic bone marrow transplantation of mesenchymal stem cells in severe idiopathic aplastic anemia patients have also been shown to improve the effect of bone marrow stromal function (53,54).…”
Section: Remaining Problems and Future Directionsmentioning
confidence: 99%
“…Die minimal-invasive Frakturfixation wird bei Kleintieren schon seit einigen Jahren praktiziert (Palmer 1999, Pozzi et al 2013 (Jang et al 2008, Fayaz et al 2011, Rolim Filho et al 2013, Ferris et al 2014 …”
Section: Minimal-invasive Implantationstechnikunclassified